A question of justice: Critically researching suicide with Indigenous studies of affect, biosociality, and land-based relations. (January 2022) - Ansloos, Jeffrey; Peltier, Shanna
This paper considers how Indigenous studies can inform the evolution of critical research on suicide. Aligned with critiques of mainstream suicidology, these methodological approaches provide a roadmap for structural analysis of complex systems and logics in which the phenomenon of suicide emerges. Moving beyond mere naming of social determinants of suicide and consistent with calls for a theory of justice within suicide research, Indigenous studies helps to advance conceptual knowledge of suicide in descriptive means and enhance ethical responses to suicide beyond psychocentric domains. Through centering Indigenous theories of affect, biosociality, and land-based relations, this article examines what new knowledge of suicide can emerge, as well as what ethical responses are possible to suicide and to a world where suicide exists. This new knowledge can inform practices for critical suicide studies which are invested in resisting structural violence, nourish agency, dignity and freedom for those living and dying in often-unlivable presents, and enhancing livability for individuals, communities, and the environment living under shadows of empire. Implications for theory, ethics, and suicide research and prevention practice are considered.